2021
DOI: 10.26633/rpsp.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the determinants and outcomes of intimate partner violence during pregnancy for Guyanese women: Results from a nationally representative cross-sectional household survey

Abstract: Objective. To determine predictors associated with physical violence during pregnancy, and to determine the relationship between exposure to intimate partner violence during pregnancy and women’s health and suicide ideation in Guyana. Methods. A secondary data analysis of a cross-sectional household survey. Multivariate logistic regression models were fitted to the data to estimate the association between physical violence during pregnancy, controlling partner behavior, and other predictors. Ordered logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Sexual violence puts women at risk for a variety of disorders, including mental illness and post-traumatic stress disorder. These have an overall negative impact on women's health [1,3,4]. Furthermore, sexual IPV increases the risk of an unplanned, mistimed, or unintended pregnancy among women, who lack access to family planning methods [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual violence puts women at risk for a variety of disorders, including mental illness and post-traumatic stress disorder. These have an overall negative impact on women's health [1,3,4]. Furthermore, sexual IPV increases the risk of an unplanned, mistimed, or unintended pregnancy among women, who lack access to family planning methods [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A 2021 study [ 23 ] conducted in Guyana on the self-reported health outcomes of females aged 15–64 years associates intimate partner violence with higher odds of suicidal ideation (95% CI: 2.48–6.76; p < 0.001), as well as higher odds of poorer reported overall health (95% CI: 1.00–2.24; p < 0.05) in women during pregnancy. This study associates increased likelihood of intimate partner violence with factors such as controlling partner behavior, being unmarried, previous experience of physical violence during childhood, and alcohol abuse by the relationship partner.…”
Section: Discussionmentioning
confidence: 99%
“…When considering that situations of violence during pregnancy are also risk factors for the life of the newborn, since this situation is associated with adverse health outcomes for the woman-child binomial, it is suggested the need for prevention of intimate partner violence and the integration of screening and treatment of intimate partner violence in prenatal care, reproductive health services and maternal and child health programs and services to identify and treat women at risk (Miller & Contreras-Urbina, 2021).…”
Section: Discussionmentioning
confidence: 99%